Quantitative Assessment of the Cryolipolysis Method for Body Contouring in Asian Patients - Nishikawa A; Aikawa Y (Dove Medical Press, 2021)
Ayaka Nishikawa,1 Yoshiyuki Aikawa2 1Cosmetic Dermatology, SBC Medical Group, Medical Corporation Shoubikai, Shinjuku-ku Tokyo, Japan; 2Cosmetic Surgery, SBC Medical Group, Shinjuku-ku Tokyo, JapanCorrespondence: Yoshiyuki Aikawa Tel +81-90-9976-9151Email 6287komatsu@sbc.or.jpPurpose: Cryolipolysis has been demonstrated to be a safe and efficient non-invasive treatment modality for reducing subcutaneous discrete areas of fat; however, only limited studies have focused on body contouring in Asian patients. The present work focuses on the quantitative assessment of the cryolipolysis method for body contouring in Asian patients.Patients and Methods: The retrospective study evaluated the medical records of 4122 patients with body contouring who underwent cryolipolysis treatment in multiple centers across Japan from January 2019 to June 2019. We evaluated the demographic profiles, treatment areas, and safety assessments among these 4122 patients. The effectiveness of the treatment was assessed in 146 patients at one of the clinics, Shonan Beauty Clinic, out of which 54 and 27 had treatments in the abdomen and upper arm areas, respectively. Clinical outcomes were assessed based on patient surveys, circumference measurements, and assessment of photographs.Results: Evaluation of choice for treatment area suggested that men generally focused more on the surrounding areas of the abdomen, while women even had options for the abdomen and the upper arm. No long-term side effects were observed during the study period. There was a significant reduction in the circumference of both the abdomen and upper arm areas (P < 0.05). Additionally, 16.7% and 18.5% of patients who had received treatment on their abdomen and upper arm, respectively, returned for the next sessions within six months. Patients who had received treatment on their upper arms were more satisfied in the categories of pain and bruising and treatment effectiveness compared to those who had received treatment on their abdomen.Conclusion: Based on the results obtained in this retrospective study on Asian patients, it can be stated that cryolipolysis is a safe and well-tolerated nonsurgical fat-reduction procedure. Clinical effectiveness can be consistently achieved with proper patient evaluation and patient satisfaction.Keywords: cryolipolysis, body contouring, retrospective study, Asian patients, non-invasive technique, safety testing